2003
DOI: 10.1002/mabi.200390041
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Graft Chitosan Derivatives

Abstract: Graft chitosan derivatives (CMCTS‐g‐MAAS and CMCTS‐g‐AAS) were prepared by the graft copolymerization of methacrylic acid sodium (MAAS) and acrylic acid sodium (AAS) onto the etherification product of chitosan‐carboxymethyl chitosan (CMCTS). Their antioxidant activity was estimated as superoxide anion scavengers by chemiluminescence techniques. The derivatives with low grafting percentages have a relatively low 50% inhibition concentration (IC50), which could be related to the fact that they have different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In our experiments, the scavenging activity of the samples of crosslinked chitosan deposed on cotton, measured at the same concentration as the samples having VT, was almost zero (results are in concordance with the above mentioned literature data [40][41][42][43]; hence all antioxidant activity determined was produced by the VT included into the chitosan-coated supports.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In our experiments, the scavenging activity of the samples of crosslinked chitosan deposed on cotton, measured at the same concentration as the samples having VT, was almost zero (results are in concordance with the above mentioned literature data [40][41][42][43]; hence all antioxidant activity determined was produced by the VT included into the chitosan-coated supports.…”
Section: Resultssupporting
confidence: 87%
“…Only at very high concentrations can chitosan scavenge superoxide anions. This may be related to the formation of strong intermolecular and intra-molecular hydrogen bonds that inhibited the reactivity of hydroxyl and amino groups in the polymer chains [41]. Some authors reported an important antioxidant activity for Low Molecular Weight (LWM) chitosan [42] and LMW and soluble Medium Molecular Weight chitosan with a 98.50% N-deacetylation [43].…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that chitosan and its derivatives act as antioxidants by scavenging oxygen radicals such as hydroxyl, superoxide, alkyl as well as highly stable DPPH radicals tested in vitro [ 204 ]. Sun and collaborators [ 205 ] reported that chitosan and their derivatives act as hydrogen donors to prevent the oxidative sequence.…”
Section: Relation Between Chemical Structure and Biological Activimentioning
confidence: 99%
“…The data suggested that N -CESC can be utilized to produce chitosan derivatives with good biochemical characteristics in vitro [ 75 ]. Graft chitosan derivatives with low grafting percentages, produced by graft copolymerization of methacrylic acid sodium and acrylic acid sodium onto the etherification product of chitosan-carboxymethyl chitosan, exhibit a relatively low 50% inhibition concentration (IC 50 ) for their radical scavenging activity, which could be attributed to their different contents of hydroxyl and amino groups in the polymer chains [ 76 ].…”
Section: Bioactivities Of Chitosanmentioning
confidence: 99%